2007
DOI: 10.4161/pri.1.2.4665
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Control of the Formation and Propagation of the [PSI+] Prion of Yeast

Abstract: It is over 40 years since it was first reported that the yeast Saccahromyces cerevisiae contains two unusual cytoplasmic 'genetic' elements: [PSI(+)] and [URE3]. Remarkably the underlying determinants are protein-based rather than nucleic acid-based, i.e., that they are prions, and we have already learnt much about their inheritance and phenotypic effects from the application of 'classical' genetic studies alongside the more modern molecular, cellular and biochemical approaches. Of particular value has been th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 80 publications
(67 reference statements)
0
21
0
Order By: Relevance
“…Comparing the ratio of ␤-galactosidase to luciferase activity with that from a second reporter lacking the stop codon gave a measure of the efficiency of translation termination. During our further analysis of the ipk1⌬ strain, we found that several of the original parental strains used in Bolger et al (33) were infected with Psi (⌿), a prion form of the Sup35 termination factor (53). To address this issue, we undertook curing of the PSI ϩ strains by growth on medium containing guanidine hydrochloride (39) and retested the strains in termination assays.…”
Section: Conserved Gle1 Residues Lysmentioning
confidence: 99%
“…Comparing the ratio of ␤-galactosidase to luciferase activity with that from a second reporter lacking the stop codon gave a measure of the efficiency of translation termination. During our further analysis of the ipk1⌬ strain, we found that several of the original parental strains used in Bolger et al (33) were infected with Psi (⌿), a prion form of the Sup35 termination factor (53). To address this issue, we undertook curing of the PSI ϩ strains by growth on medium containing guanidine hydrochloride (39) and retested the strains in termination assays.…”
Section: Conserved Gle1 Residues Lysmentioning
confidence: 99%
“…The Sup35 protein of some organisms is capable of a conformational change and self-aggregation to form prions, an infectious amyloid state [extensive body of work reviewed by (Serio and Lindquist 1999; Uptain and Lindquist 2002; Tuite and Cox 2007; Prusiner 2013)]. The Sup35 aggregates are less soluble and less functional, and thereby cause an increased rate of read-through at stop codons (increased nonsense suppression).…”
Section: Discussionmentioning
confidence: 99%
“…2) is required for the propagation of the aggregated prion state of Sup35p, and the number of such repeats can influence the frequency of both de novo and seeded formation of the [PSI + ] prion. 95 Furthermore, a single amino acid substitution in one of these repeats leads to a defect in the ability to propagate the prion form of Sup35p (i.e., [PSI + ]) but not aggregation of Sup35p per se. Yet it has been suggested that the key feature of this region, and the equivalent PrD in Ure2p (residues 1-93), is the amino acid composition and not the primary amino acid sequence.…”
Section: Relationship Between Prion Particles Structure and Infectivitymentioning
confidence: 99%